Women’s Risk Perceptions and Willingness to Engage in Risk-Reducing Interventions for the Prevention of Obesity-Related Endometrial Cancer - Derbyshire AE; MacKintosh ML; Pritchard CM; Pontula A; Ammori BJ; Syed AA; Beeken RJ; Crosbie EJ (Dove Medical Press, 2022)
Abigail E Derbyshire,1 Michelle L MacKintosh,1 Christina M Pritchard,1 Arya Pontula,2 Basil J Ammori,3,4 Akheel A Syed,4,5 Rebecca J Beeken,6 Emma J Crosbie1,2 1Department of Obstetrics and Gynaecology, Manchester University NHS Foundation Trust, Manchester, UK; 2Division of Cancer Sciences, University of Manchester, Manchester, UK; 3Department of Surgery, Salford Royal NHS Foundation Trust, Salford, UK; 4Division of Diabetes, Endocrinology and Gastroenterology, University of Manchester, Manchester, UK; 5Department of Obesity Medicine, Diabetes & Endocrinology, Salford Royal NHS Foundation Trust, Salford, UK; 6Leeds Institute of Health Sciences, University of Leeds, Leeds, UKCorrespondence: Emma J CrosbieDivision of Cancer Sciences, University of Manchester, Manchester, UK, Tel +44 161 701 6942, Email emma.crosbie@manchester.ac.ukIntroduction: Endometrial cancer rates are rising in parallel with the global obesity epidemic. Our aim was to assess the willingness of women at greatest risk of obesity-related endometrial cancer to engage with risk-reducing strategies and establish perceived barriers that may preclude their participation in a randomized controlled trial of primary endometrial cancer prevention.Materials and Methods: Women attending gynecology, obesity and sleep apnea clinics in Manchester Academic Health Sciences Centre-affiliated hospitals with obesity classes II (BMI 35- 39.9kg/m2) and III (BMI ≥ 40kg/m2) were invited to participate in a cross-sectional survey. We asked women about their perceived risk, knowledge of risk factors and willingness to engage with endometrial cancer risk-reducing interventions.Results: Seventy-four women with a median age of 51 years (range 22- 73) and BMI of 47kg/m2 (range 34- 81) took part in the study. Two-thirds (65.6%) knew that obesity was a risk factor for endometrial cancer but few were able to recall other major risk factors. Just over half (53.5%) perceived their risk of developing endometrial cancer to be higher than average. Women were prepared to lose weight (94%), eat healthily (91%), exercise more (87%), take a pill every day (74%) or receive an intra-uterine device (49%) for primary endometrial cancer prevention. Perceived barriers included cost, forgetting, willpower, finding time, physical fitness, social anxiety, possible side effects and previous bad experiences.Conclusion: Women at highest risk of obesity-related endometrial cancer may not always appreciate their susceptibility. However, willingness to engage in risk-reducing strategies suggests recruitment to a randomized controlled trial for primary endometrial cancer prevention could be feasible.Keywords: endometrial cancer, obesity, risk reducing interventions, weight loss, exercise, chemoprevention, levonorgestrel-releasing intrauterine system, metformin